2018
DOI: 10.1177/2284240318807726
|View full text |Cite
|
Sign up to set email alerts
|

A budget impact analysis of a clinical medication review of patients in an Irish university teaching hospital

Abstract: To measure the net benefit of a pharmacist-led medication review in acute public hospitals. To identify and measure the resources used when completing a pharmacist-led medication review, an observational study was conducted in an acute urban university teaching hospital. Health Information and Quality Authority guidelines were used to value resources used in a pharmacist-led medication review. Model inputs included demographic data, probability of adverse drug events associated with the pharmacist intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
2
1
1
Order By: Relevance
“…In this study, 66.37% of the PIs had a medium or high likelihood of causing an ADE, which is higher than the other similar studies, which had values of 28.7% [14] and 60.7% [54]. Whilst it could be argued that the Kearney et al study yielded similar results [54], the Gallagher et al study is a lot lower [14]. Upon further inspection however, this study was based upon a random sample of interventions (n = 100) which were then reviewed by two academic pharmacists with hospital pharmacy experience, rather than by five raters, including a GP, as in our study [14].…”
Section: Cost Analysiscontrasting
confidence: 72%
See 2 more Smart Citations
“…In this study, 66.37% of the PIs had a medium or high likelihood of causing an ADE, which is higher than the other similar studies, which had values of 28.7% [14] and 60.7% [54]. Whilst it could be argued that the Kearney et al study yielded similar results [54], the Gallagher et al study is a lot lower [14]. Upon further inspection however, this study was based upon a random sample of interventions (n = 100) which were then reviewed by two academic pharmacists with hospital pharmacy experience, rather than by five raters, including a GP, as in our study [14].…”
Section: Cost Analysiscontrasting
confidence: 72%
“…A similar study by Gallagher et al reported a cost benefit ratio of 8.64:1 [14]. Another similar study in Ireland, found that the MR provided resulted in a cost benefit ratio of 13.66:1 [54]. In this study, 66.37% of the PIs had a medium or high likelihood of causing an ADE, which is higher than the other similar studies, which had values of 28.7% [14] and 60.7% [54].…”
Section: Cost Analysissupporting
confidence: 43%
See 1 more Smart Citation
“…This is the rst study to have strati ed STOPPFrail-de ned PIMs according to the pADE occurring, which helps demonstrate PIMs that pose the greatest risk and which should be prioritised for deprescribing in frail older adults. Over one third of PIMs were rated as either 'medium' (32.4%) or 'high' (4.5%) for the pADE occurring, which is similar to the range of 2.0-66.4% reported in similar studies [21,31,33,40,41]. However, PIMs in this study were most commonly rated as having a 'very low' pADE occurring (43.7%), which is higher compared to these similar studies.…”
Section: Discussionsupporting
confidence: 76%